2009
DOI: 10.1186/1743-8977-6-31
|View full text |Cite
|
Sign up to set email alerts
|

Pathway focused protein profiling indicates differential function for IL-1B, -18 and VEGF during initiation and resolution of lung inflammation evoked by carbon nanoparticle exposure in mice

Abstract: BackgroundCarbonaceous nanoparticles possess an emerging source of human exposure due to the massive release of combustion products and the ongoing revolution in nanotechnology. Pulmonary inflammation caused by deposited nanoparticles is central for their adverse health effects. Epidemiological studies suggest that individuals with favourable lung physiology are at lower risk for particulate matter associated respiratory diseases probably due to efficient control of inflammation and repair process. Therefore w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 69 publications
(72 reference statements)
2
42
2
Order By: Relevance
“…2), which indicate a failure of particle clearance. In contrast, we have shown in previous instillation studies, with similar dosing but spherical carbon nanoparticles, that the respective acute pulmonary inflammatory response is completely resolved within 7 days at the cellular and molecular level [10]. Notwithstanding that even in the latter case, considerable amounts of the carbon nanoparticle agglomerates remain in the lungs as well but do not induce giant cell formation.…”
Section: Proposed Scheme Of Inflammatory Responsecontrasting
confidence: 67%
See 2 more Smart Citations
“…2), which indicate a failure of particle clearance. In contrast, we have shown in previous instillation studies, with similar dosing but spherical carbon nanoparticles, that the respective acute pulmonary inflammatory response is completely resolved within 7 days at the cellular and molecular level [10]. Notwithstanding that even in the latter case, considerable amounts of the carbon nanoparticle agglomerates remain in the lungs as well but do not induce giant cell formation.…”
Section: Proposed Scheme Of Inflammatory Responsecontrasting
confidence: 67%
“…In this context, 'frustrated phagocytosis' has been considered as the underlying mechanism of chronic toxicity of fibre-shaped materials, (e.g. asbestos or particular samples of multi-walled carbon nanotubes), which follow the classical fibre pathogenicity paradigm [10,38]. For less rigid tubes like single-and double-walled carbon nanotubes, as investigated in this study, a rather curled but not needle-shaped agglomerate structure was observed (Fig.…”
Section: Dwcnt Agglomerate Uptake By Alveolar Macrophages But Not By mentioning
confidence: 64%
See 1 more Smart Citation
“…Most studies have evaluated short-term (up to 7 days) or long-term (more than 14 weeks) effects on systemic outcomes, but there are very few studies evaluating medium-term effects. In an experimental study, Ganguly et al, evaluating a mouse strain (C3H/HeJ-C3) exposed to a moderately toxic carbon nanoparticle, observed elevated levels of several inflammatory chemokines in lung and/or bronchoalveolar lavage fluid at day 7 after exposure, even after complete resolution of polymorphonuclear cell influx (20). These findings suggest the possibility that such proinflammatory markers can cause systemic effects in the weeks following exposure.…”
Section: Discussionmentioning
confidence: 99%
“…It was suspended at 1 mg/ml in saline (Otsuka Pharmaceutical Factory Inc., Tokushima, Japan) with 0.05 % (v/v) Tween 80 and sonicated for more than 30 min just before administration. The carbon black can be used to examine the exclusive surface reactivity of carbon because it consists of 98% of pure carbon (Ganguly et al, 2009). The size distribution of carbon black nanoparticle in the suspension was analyzed by dynamic lightscattering using an FPAR-1000 particle analyser and the CONTIN program algorithm (Otsuka Electronics Co., Ltd., Osaka, Japan).…”
Section: Ultrafine Carbon Blackmentioning
confidence: 99%